Impact of Store Amenities on Buyers Behaviour:A Study of Convenience Goods Buyer in Organized Retail Sector in India - Das, Gopal; Vishal Kumar, Rohit (Indian Journal of Marketing, 2009)
In the Global Context of open market economics of today, the consumer has become the king. He operates through his autonomous power. He enjoys a lot of freedom in his purchase decision. A consumer is in position to influence the manufacturer or marketer regarding size, quality and contents of the product, price, and post sale service, among other things. As a result the markets have no longer remained "seller markets", it obviously turned into "buyers markets". In Indian Retail market there are so many players are entering and the growth rate is increasing. More numbers of customers are visiting organized retail mall as compare to traditional retail malls. As the more and more numbers of national and international players are entering, the competition is becoming very tuff. Everyone tries to attract more customers to their retail store. To attract customer most of the time of a year the promotions are going on for any convenience goods. But this paper tries to find out whether store amenities will be able to attract customer or not. The consumers purchase decision making process was examined with the help of structure questionnaire. The result shows that the customer is attracted by store amenities.